2019
DOI: 10.1093/ndt/gfz192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates and outcomes of absolute and functional iron deficiency anemia in nondialysis-dependent chronic kidney disease

Abstract: Background Anemia is associated with adverse outcomes in those with chronic kidney disease (CKD). We examined the association of absolute and functional iron deficiency anemia (IDA) with adverse outcomes (cardiovascular hospitalization, dialysis and mortality) in those with nondialysis-dependent CKD. Methods Nondialysis-dependent CKD patients followed in the US Veterans Administration with hemoglobin level measured within 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 32 publications
4
56
1
Order By: Relevance
“…In NDCKD patients, the US Veteran study, REport of COmorbidities in non-Dialysis Renal Disease Population in Italy (RECORD-IT), and Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDoppS) report that 21%-62% of patients have anemia, defined as Hb <12 g/dl or <12 g/dl in females and <13.5 g/dl in males, with increasing prevalence in more advanced CKD. [47][48][49] Moreover, 15%-72.8% have either ferritin <100 mg/l or TSAT <20%, and 8%-20% have both parameters below the threshold. 3,47,48,50,51 For HDCKD patients, data from United States Renal Data System 52 show that 64.5%, 14.4%, and 6.6% have Hb levels between 10-12 g/ dl, 9 and 10 g/dl, or below 9 g/dl, respectively.…”
Section: Iron Deficiency and Anemia In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…In NDCKD patients, the US Veteran study, REport of COmorbidities in non-Dialysis Renal Disease Population in Italy (RECORD-IT), and Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDoppS) report that 21%-62% of patients have anemia, defined as Hb <12 g/dl or <12 g/dl in females and <13.5 g/dl in males, with increasing prevalence in more advanced CKD. [47][48][49] Moreover, 15%-72.8% have either ferritin <100 mg/l or TSAT <20%, and 8%-20% have both parameters below the threshold. 3,47,48,50,51 For HDCKD patients, data from United States Renal Data System 52 show that 64.5%, 14.4%, and 6.6% have Hb levels between 10-12 g/ dl, 9 and 10 g/dl, or below 9 g/dl, respectively.…”
Section: Iron Deficiency and Anemia In Ckdmentioning
confidence: 99%
“…58 Moreover, TSAT <20% is also associated with cardiovascular hospitalizations and mortality. 49,54,59 However, given the association of anemia and iron deficiency with other comorbidities, the truly independent risk of abnormal Hb and/or iron levels remains uncertain.…”
Section: Iron Anemia and Outcomes In Ckdmentioning
confidence: 99%
“…This cardiomyopathy may present as ischemic heart disease or heart failure, even when arterial vascular disease is absent [ 10 ]. Anemia has been associated with an increased risk of cardiovascular events and all-cause mortality in a number of observational studies [ 11 18 ], and the American Heart Association considers anemia to be a nontraditional (non-Framingham) cardiovascular risk factor in patients with CKD [ 10 ]. In a US study of > 900,000 patients with NDD-CKD, functional iron deficiency anemia was associated with an increased risk of mortality [hazard ratio (HR) 1.11, 95% CI 1.07–1.14] and an increased relative risk (RR) of cardiovascular hospitalization after 1 year (RR 1.21, 95% CI 1.12–1.30) and 2 years (RR 1.13, 95% CI 1.07–1.21) [ 11 ].…”
Section: Disease Burdenmentioning
confidence: 99%
“…Anemia has been associated with an increased risk of cardiovascular events and all-cause mortality in a number of observational studies [ 11 18 ], and the American Heart Association considers anemia to be a nontraditional (non-Framingham) cardiovascular risk factor in patients with CKD [ 10 ]. In a US study of > 900,000 patients with NDD-CKD, functional iron deficiency anemia was associated with an increased risk of mortality [hazard ratio (HR) 1.11, 95% CI 1.07–1.14] and an increased relative risk (RR) of cardiovascular hospitalization after 1 year (RR 1.21, 95% CI 1.12–1.30) and 2 years (RR 1.13, 95% CI 1.07–1.21) [ 11 ]. Similarly, a Danish study of patients with dialysis-dependent-CKD (DD-CKD) and NDD-CKD found that anemia was associated with increased risks of major adverse cardiovascular events (MACE), acute hospitalization, and all-cause death [ 12 ], and a Japanese study of NDD-CKD patients reported that isolated anemia and iron deficiency anemia were associated with increased risks of cardiovascular-related and all-cause mortality [ 13 ].…”
Section: Disease Burdenmentioning
confidence: 99%
“… 8 There are well-established serious consequences associated with anemia in CKD, including CKD progression, cardiovascular disease, and increased mortality risk. 6 , 9–11 The presence of anemia with CKD is also associated with reduced health-related quality of life (HRQoL). 12 …”
Section: Introductionmentioning
confidence: 99%